2022
DOI: 10.1029/2022wr032182
|View full text |Cite
|
Sign up to set email alerts
|

Causes and Factors of Cryogenic Extraction Biases on Isotopes of Xylem Water

Abstract: Plant transpiration is the largest contributor to continental water flux (Jasechko, 2018;Jasechko et al., 2013). Understanding the sources of transpiration water is important for predicting the effects of global change on water security and ecosystem services. Stable isotope tracing is one of the most useful tools for the aforementioned purpose (Evaristo et al., 2015;Sprenger et al., 2016). A central assumption in the use of stable isotopes to investigate plant water sources is that, excluding leaf-evaporative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 68 publications
5
34
1
Order By: Relevance
“…The cryogenic vacuum distillation extraction method has been the most widely used analytical technique for tracing plant water sources (e.g., Amin et al, 2020; Barbeta et al, 2020; Brooks et al, 2010; Hervé‐Fernández et al, 2016). From a physicochemical perspective, cryogenic vacuum distillation is an invasive water extraction technique that certainly results in high extraction efficiencies (Wen et al, 2022). However, in soil and plant samples, the cryo‐extracted water inexorably reflects a combination (of unknown proportions) between chemically bounded water (i.e., immobile mineralogical or biological water) and soil/xylem mobile water (i.e., the analyte of interest involved in the evapotranspiration process) (von Freyberg et al, 2020, and references therein).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cryogenic vacuum distillation extraction method has been the most widely used analytical technique for tracing plant water sources (e.g., Amin et al, 2020; Barbeta et al, 2020; Brooks et al, 2010; Hervé‐Fernández et al, 2016). From a physicochemical perspective, cryogenic vacuum distillation is an invasive water extraction technique that certainly results in high extraction efficiencies (Wen et al, 2022). However, in soil and plant samples, the cryo‐extracted water inexorably reflects a combination (of unknown proportions) between chemically bounded water (i.e., immobile mineralogical or biological water) and soil/xylem mobile water (i.e., the analyte of interest involved in the evapotranspiration process) (von Freyberg et al, 2020, and references therein).…”
Section: Discussionmentioning
confidence: 99%
“…The latter may concatenate or propagate errors in mixing calculations or modelling applications. However, the concern has been raised that this technique collects bulk stem water (sap + symplastic + capillary + fibre water), not only sap water (Allen & Kirchner, 2022; Barbeta et al, 2022; Penna et al, 2018; Song et al, 2021; Wen et al, 2022), thus hindering water source uptake through the SPAC. The centrifuge method has been previously used for extracting water for isotopic analysis (Bowers et al, 2020; Li et al, 2007; Millar et al, 2018; Orlowski, Pratt, & McDonnell, 2016; Sprenger et al, 2015; Tsuruta et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The mean difference or offset in isotopic composition between the source and extracted plant water was then determined and added to the original sample values in order to correct for the apparent CVD‐induced fractionation. Because previous studies have observed a lack of CVD‐induced fractionation in sandy soils (Chen et al, 2020; Newberry et al, 2017; Orlowski et al, 2016; Wen et al, 2022), the soils of the current study were omitted from the rewetting experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Preliminary results from the isotope analyses revealed that the plant waters were depleted in hydrogen in comparison with the respective soil waters. Some researchers have suggested that the CVD method introduces considerable depletion of the hydrogen in plant water (Barbeta et al, 2019(Barbeta et al, , 2020Chen et al, 2020;Newberry et al, 2017;Wen et al, 2022;Zhao et al, 2016). In order to address any offset and correct for CVD-induced hydrogen fractionation, a rewetting experiment was performed on previously extracted pine tree samples following the method outlined in Chen et al (2020).…”
Section: Water Stable Isotopesmentioning
confidence: 99%
“…for a range of conifer species Wen et al (2022). found large variations in the δD of xylem water between apple Distribution of mean δD biases per tree species.…”
mentioning
confidence: 92%